Intersecting Film, Music, and Queerness - Dubowsky, Jack Curtis; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Intersecting Film, Music, and Queerness uses musicology and queer theory to uncover meaning and message in canonical American cinema. This study considers how queer readings are reinforced or nuanced through analysis of musical score. Taking a broad approach to queerness that questions heteronormative and homonormative patriarchal structures, binary relationships, gender assumptions and anxieties, this book challenges existing interpretations of what is progressive and what is retrogressive in cinema. Examined films include Bride of Frankenstein, Louisiana Story, Rudolph the Red-Nosed Reindeer, Blazing Saddles, Edward Scissorhands, Brokeback Mountain, Boys Don't Cry, Transamerica, Thelma & Louise, Go Fish and The Living End, with special attention given to films that subvert or complicate genre. Music is analyzed with concern for composition, intertextual references, absolute musical structures, song lyrics, recording, arrangement, and performance issues. This multidisciplinary work, featuring groundbreaking research, analysis, and theory, offers new close readings and a model for future scholarship. .
Keywords: Science; Science; Science, general; Electronic books